Differential sleep/wake response and sex differences following acute suvorexant, MK‐1064 and zolpidem administration in the rTg4510 mouse model of tauopathy. (23rd February 2022) - Keenan, Ryan J.; Daykin, Heather; Chu, Jiahui; Cornthwaite‐Duncan, Linda; Allocca, Giancarlo; Hoyer, Daniel; Jacobson, Laura H.
Abstract : Background and Purpose: Transgenic mouse models of tauopathy display prominent sleep/wake disturbances which manifest primarily as a hyperarousal phenotype during the active phase, suggesting that tau pathology contributes to sleep/wake changes. However, no study has yet investigated the effect of sleep‐promoting compounds in these models. Such information has implications for the use of hypnotics as potential therapeutic tools in tauopathy‐related disorders. Experimental Approach: This study examined polysomnographic recordings in 6‐6.5‐month‐old male and female rTg4510 mice following acute administration of suvorexant (50 mg·kg −1 ), MK‐1064 (30 mg·kg −1 ) or zolpidem (10 mg·kg −1 ), administered at the commencement of the active phase. Key Results: Suvorexant, a dual OX receptor antagonist, promoted REM sleep in rTg4510 mice, without affecting wake or NREM sleep. MK‐1064, a selective OX2 receptor antagonist, reduced wake and increased NREM and total sleep time. MK‐1064 normalised the hyperarousal phenotype of male rTg4510 mice, whereas female rTg4510 mice exhibited a more transient response. Zolpidem, a GABAA receptor positive allosteric modulator, decreased wake and increased NREM sleep in both male and female rTg4510 mice. Of the three compounds, the OX2 receptor antagonist MK‐1064 promoted and normalised physiologically normal sleep, especially in male rTg4510 mice. Conclusions and Implications: Our findings indicate that hyperphosphorylated tau accumulation and associated hyperarousal does not significantly alter the responses of tauopathy mouse models to hypnotics. However, the sex differences observed in the sleep/wake response of rTg4510 mice to MK‐1064, but not suvorexant or zolpidem, raise questions about therapeutic implications for the use of OX2 receptor antagonists in human neurodegenerative disorders.